2022
DOI: 10.3389/fphar.2022.968223
|View full text |Cite
|
Sign up to set email alerts
|

LINC-PINT suppresses cisplatin resistance in gastric cancer by inhibiting autophagy activation via epigenetic silencing of ATG5 by EZH2

Abstract: Resistance to cisplatin (DDP) is a major obstacle in the clinical treatment of advanced gastric cancer (GC). Long noncoding RNA (lncRNA) play a significant regulatory role in the development and drug resistance of GC. In this study, we reported that the lncRNA LINC-PINT was downregulated in DDP-resistant GC cells. Functional studies showed that LINC-PINT inhibited proliferation and migration of DDP-resistant GC cells in vitro, and overexpression of LINC-PINT could enhance the sensitivity of DDP-resistant GC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Drug tolerance remains a barrier to eligibility for cancer chemotherapy, and resistance to cisplatin is a major handicap to the clinical treatment of late-stage gastric cancer [ 17 ]. To test whether YTHDF2 overexpression influenced cisplatin resistance, HGC27 and MGC803 cells with YTHDF2 stable overexpression (LV-YTHDF2) were cultured with cisplatin followed by colony formation assays and we found that YTHDF2 overexpression increased the cisplatin sensitivity of GC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drug tolerance remains a barrier to eligibility for cancer chemotherapy, and resistance to cisplatin is a major handicap to the clinical treatment of late-stage gastric cancer [ 17 ]. To test whether YTHDF2 overexpression influenced cisplatin resistance, HGC27 and MGC803 cells with YTHDF2 stable overexpression (LV-YTHDF2) were cultured with cisplatin followed by colony formation assays and we found that YTHDF2 overexpression increased the cisplatin sensitivity of GC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the expression of PINT was found to be reduced in cases of colorectal cancer, whereas increased expression of PINT was observed to hinder the proliferation of tumor cells [ 47 ]. Subsequent investigations have provided additional evidence indicating that long non-coding RNA PINT has a regulatory influence on the proliferation of tumor cells and their sensitivity to radiochemotherapy across a range of malignancies [ 48 ], including gastric cancers [ 49 ], nasopharyngeal cancers [ 50 ], and skin cancers [ 51 ], and serves as a diagnostic/prognostic marker of cancer [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDDP is a first-line chemotherapeutic regimen that induces DNA damage and activates cell cycle checkpoints primarily through forming platinum-DNA polymers, leading to apoptosis of cancer cells [ 49 , 61 , 62 ]. It has been known that the MSH2- MSH6 dimer recognizes cisplatin, and its functional defects can enhance resistance to cisplatin [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In DDP-resistant GC cell lines, 12 lncRNAs were found to be involved in the regulation and promotion of invasion and metastasis. They are HOTAIR [ 60 , 61 , 62 ], HOTTIP [ 65 ], FAM84B-AS [ 48 ], KLF3-AS1 [ 69 ], SNHG6 [ 93 ], ST7-AS1 [ 106 ], LINC-PINT [ 72 ], and LINC00922 [ 73 ]. Six lncRNAs are implicated in the multidrug resistance of gastric cancer cells and facilitate the invasion and metastasis of these drug-resistant cells.…”
Section: Drug Resistance-related Lncrnas and Malignant Phenotypes In Gcmentioning
confidence: 99%